2002
DOI: 10.1161/01.cir.0000027822.23269.07
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Soluble Fas Attenuates Transplant Arteriosclerosis in Rat Aortic Allografts

Abstract: Background-The killing of vascular cells by activated macrophages is an important step in the process of destabilization of the arterial wall. The death receptor Fas is implicated in vascular cell death. Hence, we extended our studies in a rat aortic allograft model, using adenovirus-mediated overexpression of soluble Fas (sFas) to block Fas binding to Fas ligand (Fas-L). The contribution of Fas to vascular cell injury and consequent transplant arteriosclerosis was investigated. Methods and Results-Activated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…Recently, inhibition of FasL signaling in a rat model of TVD was reported to partially reduce lesion severity. 25 In addition to this cytotoxic pathway, cytokines secreted by infiltrating T cells, such as ␥-interferon, can cause TVD in the absence of cytotoxicity by indirectly inducing VSMC proliferation. 26 The immunopathological mechanisms that contribute to allograft vascular damage and resultant TVD may involve both acute and chronic rejection processes since acute rejection predicts the development of TVD in humans, and the induction of acute rejection episodes has been shown to markedly increase the severity of TVD in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, inhibition of FasL signaling in a rat model of TVD was reported to partially reduce lesion severity. 25 In addition to this cytotoxic pathway, cytokines secreted by infiltrating T cells, such as ␥-interferon, can cause TVD in the absence of cytotoxicity by indirectly inducing VSMC proliferation. 26 The immunopathological mechanisms that contribute to allograft vascular damage and resultant TVD may involve both acute and chronic rejection processes since acute rejection predicts the development of TVD in humans, and the induction of acute rejection episodes has been shown to markedly increase the severity of TVD in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…This was shown by first placing the donor heart transduced with the Bcl-2 gene in a syngeneic recipient to allow for Bcl-2 gene expression in the graft in the absence of alloimmune responses, with re-transplantation of the graft into an allogeneic recipient 4 days later. In other studies, adenoviral gene transfer of CD40Ig [59], soluble Fas receptor [60], or Fas ligand [61] partially prevented the development of graft vasculopathy. Fas ligand acts by inducing apoptosis of activated T cells that express Fas receptor on their surfaces.…”
Section: Prevention Of Graft Vasculopathymentioning
confidence: 83%
“…Luo et al (2001) found that coexpression of p35 in FasLtransduced VSMCs is more potent at inhibiting neointimal formation and as such represents an improved gene therapy approach for restenosis. Wang et al (2002) identified that blocking Fas/Fas-L interaction by overexpression of sFas in graft endothelium inhibited vascular cell apoptosis as well as CD45+ mononuclear cell infiltration, and significantly attenuated the disruption of the arterial wall and transplant arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%